Pengembangan Aplikasi General Affairs Berbasis Web Menggunakan Framework CodeIgniter Kasus PT. Rajawali Nusantara Indonesia - Efrizal, Efrizal; Tawakal, Hilmy Abidzar (DBESTI: Journal of Digital Business and Technology Innovation, 2024)
In PT. Rajawali Nusantara Indonesia (RNI) has a division that handles the general part of the company. The division is called the HR and General Strategic Services division. This division handles several work units such as maintenance of company assets (Maintenance), drivers (Drivers), and shipping or expeditions. No system takes it at delivery, so it is still handled manually. The other two, maintenance and the driver, have used a web-based system to manage it. Although there is already a system that runs it, based on the results of interviews with related experts, it still needs to improve. In this study, we will design a web-based General Affairs application using the Codeigniter framework. In the development of the application, the extreme programming method was used with the use of UML diagrams for design documentation. The application that has been made will be tested using the black box method with 100% success results from the 31 tested scenarios and User Acceptance Testing to try whether the system is by the user's wishes or not, resulting in 100% success. The result of the research is a general web-based application developed using the Codeigniter framework. Results Based on the analysis of the web-based General Affair application questionnaire results, it can help the process of operational activities at PT. RNI with good interpretation.